Optimising fisheries management in relation to tuna catches in the western central Pacific Ocean: A review of research priorities and opportunities. (September 2015) - Evans, K.; Young, J.W.; Nicol, S.; Kolody, D.; Allain, V.; Bell, J.; Brown, J.N.; Ganachaud, A.; Hobday, A.J.; Hunt, B.; Innes, J.; Gupta, A. Sen; et al.
Abstract: Some of the most important development goals for the countries and territories of the Western and Central Pacific Ocean (WCPO) involve the sustainable management of their fisheries in light of environmental, economic and social uncertainties. The responses of fish populations to variability in the marine environment have implications for decision making processes associated with resource management. There is still considerable uncertainty in estimating the responses of tuna populations to short-to-medium-term variability and longer-term change in the oceanic environment. A workshop was organised to examine how advances in oceanography, fisheries science and fisheries economics could be applied to the tuna fisheries of the WCPO and in doing so identify research priorities to improve understanding relevant to progressing management. Research priorities identified included: (i) improved parameterisation of end to end ecosystem model components, processes and feedbacks through expanded biological observations and incorporation of higher resolution climate models; (ii) development of seasonal and inter-annual forecasting tools enabling management responses to short-term variability in tuna distributions and abundances; (iii) improved understanding of the population dynamics of and the energy transfer efficiencies between food web components; (iv) assessment of the optimal value of access rights and overall fishery value under multiple scenarios of tuna distribution and abundance and influences on decision making by fisheries managers and fleets and (v) development of management strategy evaluation frameworks for utilisation in the implementing and testing of fishery management procedures and to help prioritise research directions and investment. Issues discussed and research priorities identified during the workshop have synergies with other internationally managed fisheries and therefore are applicable to many other fisheries.